2022
DOI: 10.1186/s13063-022-06636-8
|View full text |Cite
|
Sign up to set email alerts
|

Open hemorrhoidectomy under local anesthesia versus saddle block in western Uganda: a study protocol for a prospective equivalence randomized, double-blind controlled trial

Abstract: Background While open hemorrhoidectomy under local anesthesia has been shown to be more cost-effective with shorter operation times and lower complication rates, local anesthesia is still not considered as a first-line technique in low-income countries like Uganda. The objective of this trial is to compare open hemorrhoidectomy using local anesthesia versus saddle block among patients with primary uncomplicated 3rd- or 4th-degree hemorrhoids in western Uganda. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Similar findings were observed by Jinjil et al, who observed in their study that perianal block using ropivacaine 0.2% with dexmedetomidine as an adjuvant provides long-lasting postoperative analgesia and is acceptable to the surgeon. 10 Anorectal surgeries such as hemorrhoidectomy under LA have advantage of expediting return to baseline functional status and reduction in costs associated with reduced length of stay and complications similar to findings observed by Sikakulya et al, 21 Like our study, other studies have also reported no case of perianal abscess after LA technique. 20,23 Adverse effects of LA on CNS, CVS, and respiratory system after absorption are not seen in our study since we used less concentration and volume of LA and site of injection was also away from pudendal neurovascular bundle.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar findings were observed by Jinjil et al, who observed in their study that perianal block using ropivacaine 0.2% with dexmedetomidine as an adjuvant provides long-lasting postoperative analgesia and is acceptable to the surgeon. 10 Anorectal surgeries such as hemorrhoidectomy under LA have advantage of expediting return to baseline functional status and reduction in costs associated with reduced length of stay and complications similar to findings observed by Sikakulya et al, 21 Like our study, other studies have also reported no case of perianal abscess after LA technique. 20,23 Adverse effects of LA on CNS, CVS, and respiratory system after absorption are not seen in our study since we used less concentration and volume of LA and site of injection was also away from pudendal neurovascular bundle.…”
Section: Discussionsupporting
confidence: 89%
“…18,19 Some studies have used EMLA cream or 5% lignocaine-based ointment about an hour before injecting LA 10,20,21. Scarfone et al suggested that lower injection rate of LA is associated with less pain because of less rapid distension of local tissue and activation of fewer nerve endings 22.…”
mentioning
confidence: 99%
“…Moreover, since local anesthesia was given through 0.5% lignocaine and 0.25% bupivacaine, it was seen that bleeding was lesser due to the vasoconstriction effect. The same applied to the rate of complications that were significantly lesser in patients who had undergone local anesthesia for his procedure [19].…”
Section: Hemorrhoidsmentioning
confidence: 99%